Analisis Terhadap Tindakan Diluar Kewenangan Tukang Gigi Di Gorontalo Serta Pertanggungjawaban Menurut KUHP Nasional - Lamusu, Citra (Sekolah Tinggi Ilmu Hukum Sumpah Pemuda, 2026)
Nowadays, dental technicians also perform procedures outside their scope of practice, such as installing braces, teeth whitening, and dental veneers; this often leads to undesirable consequences such as prolonged pain, infection, cancer, and death. This study aims to examine the legal perspective on dentists’ actions beyond their scope of practice, along with their criminal liability under Law No. 1 of 2023 on the Criminal Code. Using a normative legal research method, the results indicate that the legal perspective on dentists’ actions beyond their scope of practice—such as IBG, IBG, and EPBG are unlawful and constitute a violation of the law; and that dental technicians who act negligently may be charged under Articles 474 and 475 of the National Criminal Code.